Open-Circuit Fault Diagnosis in Power Inverters Through Currents Analysis in Time Domain - Reyes-Malanche, Josue A.; Villalobos-Pina, Francisco J.; Cabal-Yepez, Eduardo; Alvarez-Salas, Ricardo; Rodriguez-Donate, Carlos (IEEE transactions on instrumentation and measurement, 2021)
Power inverters are essential components in modern electrical distribution systems. Switches are key elements of a power inverter, and they are the more affected components when a fault occurs. Breakdown of power-semiconductor devices represents around 38% of a power inverter fault. An open-circuit fault will keep the inverter working, jeopardizing its components and degrading its performance. The diagnosis and classification of power inverter faults have become important research subjects to avoid malfunctioning or damage of other components in an electric system. The Fourier transform and the wavelet-based multiresolution analysis (MRA) are the most applied signal processing techniques for identifying open-circuit faults in these devices. They are usually combined with other methods for increasing its effectiveness, which demands a considerable use of computational resources. This work introduces a novel low-computational-cost technique that directly analyzes the electric phase currents from a power inverter, in the time domain, utilizing three rotatory reference systems and basic arithmetic operations to identify open-circuit faults. The proposed method allows determining the specific power supply phase and the faulty switch, or switches, with high certainty. The obtained results are validated through exhaustive analyses against the Fourier transform and the wavelet-based MRA, demonstrating the proposed method suitability for online-monitoring applications, ensuring high sensitivity and accuracy on detecting and isolating open-circuit faults with low computation cost.